AN ONLINE SURVEY AMONG US PATIENTS WITH IMMUNE-MEDIATED CONDITIONS: BELIEFS ABOUT BIOSIMILARS FROM PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Jacobson, Gary; Gibofsky, Allan; O'Hara-Levi, Shannan; Franklin, Archie; Peyrin-Biroulet, Laurent; McGrath, Melissa; McCabe, Dorothy
Abstract: INTRODUCTION: This survey assessed biosimilar beliefs among patients with inflammatory bowel disease (IBD), rheumatoid arthritis (RA), psoriasis (PsO) and/or psoriatic arthritis (PsA). We report here on patients with IBD. METHODS: WebMD, LLC invited patients from the Dynata® consumer panel to participate in an online survey. US residents ≥18 years with a self-reported specialist diagnosis of IBD, RA, or PsO/A of ≥1 year were eligible. Patients with multiple conditions answered questions about 1 condition only; those with RA+IBD reported on IBD, whereas those with PsO/A+IBD reported on PsO/A, and those with RA+PsO/A reported on RA; neither the PsO/A or RA groups are included here. Those currently receiving an infliximab biosimilar were excluded. A quota of 500 was set and stratified based on US geographic region and condition (∼33% each); once quota was reached, no further surveys were administered for that region or condition. Responses were summarized descriptively. The survey received an IRB exemption by Advarra (Columbia, MD). RESULTS: Per quota, 166 patients had IBD (ulcerative colitis, 72%; Crohn's disease, 12%; both, 4%; IBD+RA, 11%). Mean age of IBD patients was 50 y; 67% were female. Overall, 36% (n=59/166) were currently on a biologic and 64% (n=107/166) were not currently on a biologic (ie, 46% [n=76/166)] were biologic naïve and 19% [n=31/166] had used biologics in the past). Among current biologic users, 61% (n=36/59) were on an anti-TNFα (adalimumab 50%; infliximab 19%; etanercept 17%). Overall, 68% (n=113/166) had not heard of a biosimilar, 22% (n=36/166) had, and 10% (n=17/166) were unsure. Current biologic users (42%) were more likely to have heard of biosimilars than those not currently using biologics (10%). Before answering additional questions, patients were shown the FDA biosimilar definition. Main concerns about biosimilars were side effects and long-term safety (Figure). Among current biologic users, 37% (n=22/59) would accept a switch to a biosimilar, 36% (n=21/59) were unsure, and 27% (n=16/59) would not switch. When those not currently using a biologic were asked their preference if their doctor prescribed a biologic, for 52% (n= 56/107) it depended on cost, 26% (n=28/107) had no preference, 11% (n=12/107) would take the biosimilar, and 10% (n= 11/107) preferred the original. When patients not currently using a biologic were asked if an original anti-TNFα was now prescribed but the insurance company required a biosimilar of that medicine, 54% (n=58/107) would accept the switch and 43% (n=46/107) were unsure. Overall, 76% of patients wanted additional information to help them learn more about biosimilars. DISCUSSION: Most patients with IBD had not heard of biosimilars and most patient's main concern was about the safety profile. Further education may help patients make informed choices about biosimilar switching or initiation.